A method for preparing yttrium oxide transparent ceramic
Through the discharge plasma sintering method and the addition of LiF, the problems of low preparation efficiency and poor optical performance of yttrium oxide transparent ceramics in the traditional sintering method are solved, and the preparation of yttrium oxide transparent ceramics with fast, efficient and excellent optical performance are achieved.
Patent Information
- Application Number
- CN202410603884.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-15
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-05-15
AI Technical Summary
The existing traditional sintering methods such as pressureless sintering, microwave sintering and hot pressing sintering When preparing yttrium oxide transparent ceramics, the temperature rise rate is slow, the insulation time is long, the sintering temperature isostatic sintering isostatic sintering equipment is expensive, the production efficiency is low, and it is not suitable for mass production.
The discharge plasma sintering method is adopted to press the transparent ceramic powder of yttrium oxide in a graphite mold, and quickly raise and insulate the heat by using a discharge plasma sintering furnace. Combined with the use of a certain amount of LiF and tantalum paper, the carburization problem is overcome and optical performance is improved.
It realizes the rapid preparation of yttrium oxide transparent ceramics, with good optical performance and high repeatability, and is suitable for mass production, solving the problems of low efficiency and poor optical performance of traditional methods.
Smart Images

Figure CN118495949B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ceramic material preparation, and in particular relates to a method for preparing yttrium oxide transparent ceramics. Background Art
[0002] Yttria transparent ceramics have many excellent properties, such as high melting point, good chemical and photochemical stability, wide optical transparency range (0.23μm~8.0μm), low phonon energy, and its maximum phonon cutoff frequency is about 550cm -1 Low phonon energy can suppress the probability of non-radiative transition and increase the probability of radiative transition, thereby improving the luminous efficiency. Due to its excellent physical and chemical properties, it is potentially developed in the fields of infrared windows and domes of missiles, visible and infrared lenses, high-pressure gas discharge lamps, ceramic scintillators, and ceramic lasers.
[0003] At present, common methods for preparing yttrium oxide transparent ceramics include pressureless sintering, microwave sintering, hot pressing sintering, hot isostatic pressing sintering and spark plasma sintering. The heating rate of yttrium oxide transparent ceramics prepared by pressureless sintering, microwave sintering and hot pressing sintering is slow and the heat preservation time is long. Hot isostatic pressing sintering samples generally need to be used in conjunction with other sintering methods. For example, Wang et al. prepared yttrium oxide transparent ceramics by vacuum sintering and hot isostatic pressing sintering. They first vacuum sintered at 1700°C for 2h, and then hot isostatically pressed at 1775°C for 4h, and finally obtained transparent ceramics with transmittances of 78.9% and 83.4% at 600nm and 2000nm, respectively (Wang J, Ma J, Zhang J, et al. Yb: Y2O3 transparent ceramics processed with hot isostatic pressing [J]. Optical Materials, 2017, 71: 117-120).
[0004] In summary, the preparation of yttrium oxide transparent ceramics by pressureless sintering, microwave sintering and hot pressing sintering has a slow heating rate, a long holding time, a high sintering temperature, a low efficiency, and the optical properties of the samples usually prepared are poor. The hot isostatic pressing sintering equipment is expensive and has low production efficiency, and is not suitable for the mass production of yttrium oxide transparent ceramics. Summary of the invention
[0005] The present invention mainly solves the problems of existing traditional sintering methods, such as pressureless sintering, microwave sintering and hot pressing sintering for preparing yttrium oxide transparent ceramics, such as slow heating rate, long insulation time, high sintering temperature, low efficiency, and usually poor optical properties of the prepared samples, expensive hot isostatic pressing sintering equipment, and low production efficiency. A method for preparing yttrium oxide transparent ceramics is provided.
[0006] The present invention is achieved through the following technical solutions.
[0007] A method for preparing yttrium oxide transparent ceramics comprises the following steps:
[0008] (i) pouring the prepared yttrium oxide transparent ceramic powder into a graphite mold, and after pressing and molding, obtaining a graphite mold with a ceramic blank in the middle;
[0009] (ii) placing the graphite mold with the ceramic blank in a spark plasma sintering furnace, then heating the temperature to 1100°C at a heating rate of 100°C / min, keeping it at 1100°C for 5 minutes, then heating it to 1450°C~1600°C at a rate of 15°C / min~20°C / min, keeping it at that temperature for 20 minutes, then cooling it to 1100°C at a rate of 100°C / min and keeping it at that temperature for 5 minutes, and then cooling it to 1100°C without grinding or polishing to obtain a ceramic block of yttrium oxide transparent ceramics after furnace cooling; wherein, the initial applied pressure is 10MPa~20MPa, and when the temperature reaches 1100°C, the pressure is increased to 75MPa~80MPa until it is kept at the sintering temperature of 1450°C~1600°C for 20 minutes;
[0010] (iii) Grinding and polishing the sintered ceramic block with sandpaper to a thickness of 1 mm to 1.1 mm to obtain yttrium oxide transparent ceramic.
[0011] Further, the chemical formula of the yttrium oxide transparent ceramic powder described in step (a) is Y 1.8 La 0.2 O3, the average particle size is between 20nm and 60nm.
[0012] Furthermore, the preparation steps of the yttrium oxide transparent ceramic powder described in step (a) are specifically as follows: a powder precursor is prepared by a chemical coprecipitation method, the prepared precursor is calcined at 900°C for 2h, the calcined powder is poured into anhydrous ethanol, 0wt% to 2wt% LiF is added and stirred for 6h, and then filtered, dried and sieved to obtain the prepared yttrium oxide transparent ceramic powder.
[0013] Furthermore, the preparation method of the precursor is as follows: Y2O3 and La2O3 are poured into distilled water at a molar ratio of 9:1 and heated. When it starts to boil, nitric acid is added to react fully until it becomes transparent and colorless. The concentration of the Y(NO3)3 and La(NO3)3 solutions obtained after the reaction is configured to be 0.1 mol / L. NH4OH and NH4HCO3 are used as precipitants at a molar ratio of 1:1. 3wt% PEG2000 is added as a dispersant to configure a solution with a concentration of 1 mol / L. The configured Y(NO3)3 and La(NO3)3 solutions are then added dropwise to the precipitant which is stirred continuously. The titration rate is less than 2 ml / min, and the pH value during the titration is controlled between 9 and 10. After the titration is completed, the desired precursor is obtained after aging, filtration and drying. The aged precipitate needs to be cleaned with distilled water and anhydrous ethanol during the filtration process. The distilled water is used for cleaning 4 to 5 times and the anhydrous ethanol is used for cleaning 3 to 4 times.
[0014] Furthermore, in the powder loading process in step (i), a thin layer of tantalum paper should be placed on the inner wall of the graphite mold, a piece of tantalum paper should be placed at the lower end, the powder should be placed in the mold, and then a piece of tantalum paper should be placed at the upper end to separate the graphite mold from the powder.
[0015] Furthermore, the pressing process described in step (i) is to apply pressure to the upper and lower pressure heads of the graphite mold, the pressure is 15 MPa, and the pressure holding time is 10 minutes.
[0016] Compared with the prior art, the advantages of the present invention are: the present invention adopts a sintering method of spark plasma sintering, which has a fast heating rate (heating rate of 15°C / min to 100°C / min) and a short holding time compared with pressureless sintering, atmosphere sintering, microwave sintering and other sintering methods. While ensuring its high efficiency, the common carburization problem of spark plasma sintering is overcome by adding a certain amount of LiF and replacing the graphite paper commonly used to wrap the powder in the graphite mold with tantalum paper, thereby causing the optical performance to decrease. The preparation time of yttrium oxide transparent ceramics prepared by this method is short, the operation is simple, the optical performance is good, the repeatability is high, and it is suitable for mass production, providing a new preparation method for rapidly preparing yttrium oxide transparent ceramics with excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The figure is a flow chart of the preparation of the yttrium oxide transparent ceramic of Example 1;
[0018] Figure 2 is the X-ray diffraction pattern of the yttrium oxide transparent ceramic of Example 1;
[0019] Figure 3 This is a photo of the yttrium oxide transparent ceramic of Example 1 after polishing;
[0020] Figure 4This is a microscopic structural photograph of the surface of the yttrium oxide transparent ceramic of Example 1 after polishing and acid etching;
[0021] Figure 5 This is the transmittance curve of the yttria transparent ceramic of Example 1 after polishing. DETAILED DESCRIPTION
[0022] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.
[0023] Specific implementation method 1: This implementation method is a method for preparing yttrium oxide transparent ceramics, which is carried out according to the following steps:
[0024] (i) pouring the prepared yttrium oxide transparent ceramic powder into a graphite mold, and after pressing and molding, obtaining a graphite mold with a ceramic blank in the middle;
[0025] (ii) Place the graphite mold with the ceramic blank in a spark plasma sintering process, then heat it to 1100°C at a heating rate of 100°C / min, keep it at 1100°C for 5 minutes, then heat it to 1450°C~1600°C at 15°C / min~20°C / min, keep it at that temperature for 20 minutes, then cool it to 1100°C at 100°C / min and keep it at that temperature for 5 minutes, and then cool it to 1100°C at 100°C / min to obtain a ceramic block of yttrium oxide transparent ceramic without grinding and polishing after furnace cooling. The initial pressure applied is 10MPa~20MPa, and when the temperature reaches 1100°C, the pressure increases to 75MPa~80MPa until it is kept at 1450°C~1600°C for 20 minutes.
[0026] (iii) Grinding and polishing the obtained yttrium oxide ceramic block to a thickness of 1 mm to 1.1 mm using sandpaper to obtain yttrium oxide transparent ceramic.
[0027] The advantages of the present invention are: the present invention adopts a sintering method of spark plasma sintering, which has a fast heating rate (the fastest heating rate used in this experiment is 100°C / min) and a short holding time compared to sintering methods such as pressureless sintering, atmosphere sintering, and microwave sintering. While ensuring its high efficiency, the present invention overcomes the common carburization problem of spark plasma sintering by adding a certain amount of LiF and replacing the graphite paper commonly used to wrap the powder in the graphite mold with tantalum paper, thereby causing the optical performance to decrease. The preparation time of yttrium oxide transparent ceramics prepared by this method is short, the operation is simple, the optical performance is good, the repeatability is high, and it is suitable for mass production, providing a new preparation method for the rapid preparation of yttrium oxide-based transparent ceramics with excellent performance.
[0028] Specific embodiment 2: This embodiment is different from the specific embodiment 1 in that the chemical formula of the yttrium oxide transparent ceramic powder described in step (1) is Y1.8 La 0.2 O3, the average particle size is 20nm to 60nm. Other details are the same as those in the first embodiment.
[0029] Specific embodiment 3: This embodiment is different from specific embodiment 1 and embodiment 2 in that the preparation step of the yttrium oxide transparent ceramic powder described in step (1) is as follows: a precursor of the powder is prepared by chemical coprecipitation method, the prepared precursor is calcined at 900°C for 2h, the calcined powder is poured into anhydrous ethanol, 0wt% to 2wt% LiF is added and stirred for 6h, and then filtered, dried and sieved to obtain the prepared yttrium oxide transparent carbon ceramic powder. The rest is the same as specific embodiments 1 to 2.
[0030] The purity of the anhydrous ethanol described in this specific embodiment is analytical grade.
[0031] The following examples are used to verify the beneficial effects of the present invention:
[0032] Embodiment 1:
[0033] A method for preparing yttrium oxide-based transparent ceramics, characterized in that the preparation is carried out through the following steps:
[0034] (i) Pour the prepared yttrium oxide transparent ceramic powder into a graphite mold, and after pressing and molding, obtain a graphite mold with a ceramic blank in the middle.
[0035] (ii) Place the graphite mold with the ceramic blank in a spark plasma sintering furnace, then heat it to 1100°C at a heating rate of 100°C / min, keep it at 1100°C for 5 minutes, then heat it to 1550°C at 15°C / min, keep it at that temperature for 20 minutes, then cool it to 1100°C at 100°C / min and keep it at that temperature for 5 minutes, and then cool it to 1100°C at 100°C / min to obtain a ceramic block of yttrium oxide transparent ceramic without grinding and polishing after furnace cooling. The initial pressure applied is 15MPa, and when the temperature reaches 1100°C, the pressure increases to 80MPa until it is kept at 1550°C for 20 minutes.
[0036] (iii) Grind and polish the obtained ceramic block with sandpaper to a thickness of 1.05 mm to obtain yttrium oxide transparent ceramic.
[0037] The chemical formula of the yttrium oxide transparent ceramic powder described in step (a) is Y 1.8 La 0.2 O3, average particle size is 20nm~60nm;
[0038] The preparation steps of the yttrium oxide transparent ceramic powder described in step (a) are specifically as follows: a precursor of the powder is prepared by a chemical coprecipitation method, the prepared precursor is calcined at 900° C. for 2 h, the calcined powder is poured into anhydrous ethanol, 0.3 wt % LiF is added and stirred for 6 h, and then filtered, dried and sieved to obtain the prepared yttrium oxide transparent ceramic powder;
[0039] The preparation method of the precursor is as follows: Y2O3 and La2O3 are poured into distilled water at a molar ratio of 9:1 and heated. When the solution boils, nitric acid is added to react fully until it becomes colorless and transparent. The concentration of the Y(NO3)3 and La(NO3)3 solutions after the reaction is configured to be 0.1 mol / L. NH4OH and NH4HCO3 are precipitants, configured at a molar ratio of 1:1. 3wt% PEG2000 is added as a dispersant to configure a solution with a concentration of 1 mol / L. The configured Y(NO3)3 and La(NO3)3 solutions are then added dropwise to the precipitant which is continuously stirred. The titration rate is less than 2 ml / min, and the pH value during the titration process is controlled between 9 and 10. After the titration is completed, the desired precursor is obtained after aging, filtration and drying. The aged precipitate needs to be cleaned with distilled water and anhydrous ethanol during the filtration process. The distilled water is used for cleaning 4 times and the anhydrous ethanol is used for cleaning 3 times.
[0040] In the process of filling the powder described in step (i), a thin layer of tantalum paper should be placed on the inner wall of the graphite mold, a piece of tantalum paper should be placed at the lower end, the powder should be placed in the mold, and a piece of tantalum paper should be placed at the upper end to separate the graphite mold from the powder.
[0041] The pressing process described in step (a) is to apply pressure to the upper and lower pressure heads of the graphite mold, the pressure is 15 MPa, and the pressure holding time is 10 minutes.
[0042] The polished yttrium oxide transparent ceramic obtained in Example 1 was subjected to X-ray diffraction and transmittance tests. Figure 2 and Figure 5 As shown, the transparent ceramic is then acid-etched, and then the microstructure of the yttrium oxide transparent ceramic after acid etching is analyzed, as shown in FIG. Figure 3 .
[0043] Figure 2 This is the X-ray diffraction pattern of the yttrium oxide transparent ceramic prepared in Example 1 after polishing. It can be seen from the figure that the peak corresponding to the yttrium oxide transparent ceramic prepared in Example 1 is consistent with the peak of the Y2O3 standard PDF card, and no second phase appears.
[0044] Figure 3 This is a photo of the yttrium oxide transparent ceramic prepared in Example 1 after polishing. As can be seen from the photo, the words on the paper can be clearly seen in the yttrium oxide transparent ceramic prepared in Example 1.
[0045] Figure 4 This is a microscopic structural photograph of the surface of the yttrium oxide transparent ceramic prepared in Example 1 after polishing and acid corrosion; as can be seen from the figure, the average grain size of the yttrium oxide transparent ceramic prepared in Example 1 is 50μm to 100μm, and the structure is dense and has no pores.
[0046] Figure 5 This is the transmittance curve of the yttrium oxide transparent ceramic prepared in Example 1 after polishing: As can be seen from the figure, the relative density of the yttrium oxide transparent ceramic sample prepared in Example 1 after polishing is 99.91%, the linear transmittance at 800nm is 77.15%, and the optical performance is good.
[0047] Embodiment 2:
[0048] The chemical formula of the yttrium oxide transparent ceramic powder described in step (1) is Y2O3. According to the test method described in Example 1, a yttrium oxide transparent ceramic with a relative density of 99.91% is obtained. The polished yttrium oxide transparent ceramic can clearly see the text below the sample, and the transmittance at 800nm is 71.10%.
[0049] Embodiment three:
[0050] The chemical formula of the yttrium oxide transparent ceramic powder described in step (a) is Y2O3. In the preparation step of the yttrium oxide transparent ceramic powder, the calcined powder is poured into anhydrous ethanol, 0wt% LiF is added and stirred for 6 hours. The rest of the test method is the same as that in Example 1. After polishing, the text below the sample cannot be seen in the yttrium oxide transparent ceramic, and the transmittance at 800nm is 29.99%.
[0051] Embodiment 4:
[0052] The chemical formula of the yttrium oxide transparent ceramic powder described in step (a) is Y2O3. In the preparation step of the yttrium oxide transparent ceramic powder, the calcined powder is poured into anhydrous ethanol, 2wt% LiF is added and stirred for 6 hours. The rest of the test method is the same as that in Example 1. After polishing, the text below the sample can be slightly seen in the yttrium oxide transparent ceramic, and the transmittance at 800nm is 34.51%.
[0053] Embodiment five:
[0054] In step (ii), the temperature was kept at 1100°C for 5 minutes, and then the temperature was raised to 1450°C at a rate of 15°C / min. The remaining test methods were the same as those in Example 1. A yttrium oxide transparent ceramic with a relative density of 99.73% was obtained. The text below the sample could be seen in the polished yttrium oxide transparent ceramic, and the transmittance was 44.32% at 800nm.
[0055] Embodiment six:
[0056] In step (ii), the temperature was kept at 1100°C for 5 minutes, and then the temperature was raised to 1500°C at a rate of 15°C / min. The remaining test methods were the same as those in Example 1. A yttrium oxide transparent ceramic with a relative density of 99.85% was obtained. The text below the sample could be seen in the polished yttrium oxide transparent ceramic, and the transmittance was 48.44% at 800nm.
[0057] Embodiment seven:
[0058] In step (ii), the temperature was kept at 1100°C for 5 minutes, and then the temperature was raised to 1600°C at a rate of 15°C / min. The rest of the test method was the same as in Example 1. A yttrium oxide transparent ceramic with a relative density of 99.91% was obtained. The text below the sample can be clearly seen in the polished yttrium oxide transparent ceramic, but the sintering temperature was too high, resulting in carburization and blackening of the outer circle of the sample, and the transmittance was only 35.48%.
[0059] Embodiment eight:
[0060] In step (ii), the graphite mold with the ceramic blank is placed in a spark plasma sintering furnace, and then the temperature is raised to 1100°C at a heating rate of 100°C / min, and after being kept at 1100°C for 5 minutes, the temperature is raised to 1600°C at 20°C / min, and kept for 20 minutes, and then the temperature is lowered to 1100°C at 100°C / min and kept for 5 minutes, and the ceramic block of yttrium oxide transparent ceramic without grinding and polishing is obtained by furnace cooling. Among them, the initial pressure applied is 15MPa, and when the temperature reaches 1100°C, the pressure is increased to 75MPa until it is kept at 1600°C for 20 minutes. 0wt% LiF is added to the preparation step of yttrium oxide transparent ceramic powder described in step (i), and the rest of the test methods are the same as those in Example 1. The polished yttrium oxide transparent ceramic can see the text below the sample, but the sample is black as a whole, and the transmittance is only 30.32% at 800nm.
[0061] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing yttrium oxide transparent ceramics, characterized in that: The steps include: (i) pouring the prepared yttrium oxide transparent ceramic powder into a graphite mold, wherein the chemical formula of the yttrium oxide transparent ceramic powder is Y2O3, and after pressing and molding, obtaining a graphite mold with a ceramic blank in the middle; (ii) placing the graphite mold with the ceramic blank in a spark plasma sintering furnace, then heating the temperature to 1100°C at a heating rate of 100°C / min, keeping it at 1100°C for 5 minutes, then heating it to 1550°C at a rate of 15°C / min~20°C / min, keeping it at that temperature for 20 minutes, then cooling it to 1100°C at a rate of 100°C / min and keeping it at that temperature for 5 minutes, and then cooling it to 1100°C at a rate of 100°C / min to obtain a ceramic block of yttrium oxide transparent ceramic that has not been ground or polished after furnace cooling; wherein, the initial applied pressure is 10MPa~20MPa, and when the temperature reaches 1100°C, the pressure is increased to 75MPa~80MPa until it is kept at the sintering temperature of 1550°C for 20 minutes; (iii) grinding and polishing the sintered ceramic block with sandpaper to a thickness of 1 mm to 1.1 mm to obtain yttrium oxide transparent ceramic; The preparation steps of the yttrium oxide transparent ceramic powder described in step (i) are specifically as follows: a precursor of the powder is prepared by a chemical coprecipitation method, the prepared precursor is calcined at 900° C. for 2 hours, the calcined powder is poured into anhydrous ethanol, 0.3wt% LiF is added and stirred for 6 hours, and then filtered, dried and sieved to obtain the prepared yttrium oxide transparent ceramic powder; In the powder loading process in step (i), a thin layer of tantalum paper should be placed on the inner wall of the graphite mold, a piece of tantalum paper should be placed at the lower end, the powder should be placed in the mold, and then a piece of tantalum paper should be placed at the upper end to separate the graphite mold from the powder.
2. The method for preparing a yttrium oxide transparent ceramic according to claim 1, characterized in that: The chemical formula of the yttrium oxide transparent ceramic powder described in step (a) is replaced by Y2O3 1.8 La 0.2 O3, the average particle size is 20nm~60nm.
3. The method for preparing a yttrium oxide transparent ceramic according to claim 2, characterized in that: The preparation method of the precursor is as follows: Y2O3 and La2O3 are poured into distilled water at a molar ratio of 9:1 and heated, and nitric acid is added when boiling to fully react until transparent and colorless, and the concentration of the Y(NO3)3 and La(NO3)3 solutions obtained after the reaction is configured to be 0.1 mol / L, NH4OH and NH4HCO3 are precipitants, configured at a molar ratio of 1:1, and 3wt% PEG2000 is added as a dispersant to configure a solution with a concentration of 1 mol / L, and the configured Y(NO3)3 and La(NO3)3 solutions are added dropwise to the precipitant that is continuously stirred, and the titration rate is less than 2 mL / min, and the pH value during the titration process is controlled between 9 and 10. After the titration is completed, the desired precursor is obtained after aging, filtration, and drying. The aged precipitate needs to be cleaned with distilled water and anhydrous ethanol during the filtration process, and the distilled water is washed 4 to 5 times and the anhydrous ethanol is washed 3 to 4 times.
4. The method for preparing a yttrium oxide transparent ceramic according to claim 1, characterized in that: The pressing process described in step (i) is to apply pressure to the upper and lower pressure heads of the graphite mold, the pressure is 15 MPa, and the pressure holding time is 10 minutes.
Citation Information
Patent Citations
Method for preparing transparent yttrium oxide ceramic component through two-step pressure sintering
CN105777123A
Method for preparing transparent calcium fluoride ceramics
CN106116581A
Method for preparing TiC reinforced titanium-based composite material based on cross-linking modified sintered titanium hydride
CN112342419A
Transparent yttria ceramics and method for producing same
US4115134A